Recruitment and Selection Strategy for Employee Performance at the Tanjungpinang City Job Training Center (BLK) - Nasuha, Muhammad Rafi Akbar; Ramadhan, Aditya Rizal; Heni, Diyah Rosita (Formosa Journal of Applied Sciences, 2024)
This research discusses the large number of workers in Tanjungpinang, workers are encouraged to take part in non-formal learning and work counseling to increase their knowledge and abilities because of the pressure in the world of work on competent work effectiveness. The aim of this research is to find out how well the Tanjungpinang City BLK initiative is in reducing unemployment. To obtain data for this research, a qualitative approach was used, especially literature studies and interviews. This data shows that the Tanjungpinang City UPTD BLK program has not completely succeeded in reducing the unemployment rate. Only one of the five UPTD BLK effectiveness initiatives in Tanjungpinang City is running well. Even though the other four Tanjungpinang City BLK UPTD effectiveness projects have not been completely successful, the Tanjungpinang City BLK UPTD has been able to reduce the unemployment rate.